Knowledge of paramedic staff concerning the risk in their workplace - Kulczycka, Kinga; Mędzelewska, Katarzyna (Nursing in the 21st Century, 2012)
KNOWLEDGE OF PARAMEDIC STAFF CONCERNING THE RISK IN THEIR WORKPLACEAim. The aim of this study was to learn about the risks in the paramedic service environment.Material and methods. The research method was a diagnostic survey with the use of self-constructed questionnaire. Survey was conducted in the group of paramedic employed in Lublin region in 2012.Conclusions. The analysis of collected data showed the differences in the assessment of working conditions and risks in the workplace between paramedics working in hospitals and working in ambulances.